The Effect Of The Use Of Audio Visual Media On Story Listening Skills In Indonesian Language Class V UPT SPF SDI BTN IKIP 1 Makassar City - Tati, Andi Dewi Riang; Pratiwi, Andi Riany Putri; Nurhaedah, Nurhaedah (International Journal of Elementary School Teacher, 2024)
Audio visual media is media that can only be seen and does not contain sound elements, for example pictures, paintings, photos, and so on. (Liza Husnita 2023) Listening is a basic language skill and a stage that humans must go through, namely from childhood, which is the first and main skill that must support the other three language skills. (Ernawati & Rasna (2020) This research is an experimental research that aims to: 1) ) To find out an overview of the use of audio visual media on the learning process of class V UPT SPF SDI BTN IKIP 1 Kota Makassar, 2) To find out the description of story listening skills in the Indonesian language learning outcomes of class V UPT SPF SDI BTN IKIP 1 Kota Makassar, 3) To find out the influence of audio visual media on story listening skills on the learning outcomes of Indonesian language class V UPT SPF SDI BTN IKIP 1 Kota Makassar. This type of research is quasi experimental design using a nonequivalent control group design. The population in this study is all students of class V UPT SPF SDI BTN IKIP 1 Kota Makassar totaling 57 people with a sample of class V A as an experimental class with a total of 28 students and class V B as a control class with a total of 29 students. The variables of this study consist of the independent variable, namely the use of audio-visual media and the bound variable, namely listening skills on learning outcomes. The research procedure used is in two stages, namely the preparation stage and the implementation stage. The data collection technique of this research is by conducting observations and tests with data analysis techniques using descriptive and inferential techniques which are divided into normality tests, homogeneity and hypothesis tests. The results of the descriptive analysis show that the use of audio-visual media in the learning process results in a positive impact so that it produces a very good category. The listening skills based on the results of the posttest in the experimental class showed an increase to the medium category from the low category. Based on the results of inferential statistical analysis, a value of 0.001 < 0.05 was obtained, which means that there is a difference between the class that was given audio visual media treatment and the class that was not given treatment. Based on this, it can be concluded that the use of audio visual media is effectively used to improve students' listening skills in the learning outcomes of class V UPT SPF SDI BTN IKIP 1 Kota Makassar